Trusts on nerd immunity and health-associated apparatus predict the level of obedience of indonesians toward health resilience threat-anticipation enforced by the government - Nurlaila Ika; Amalya Dewi Meta (E3S Web of Conferences)
The global concept of One Health has gained popularity, with countries like Indonesia implementing policies to combat the pandemic. Despite this, many Indonesians have been slow to follow pandemic-related measures, such as getting vaccinated and social distancing. This study aims to investigate the connection between people’s experiences, their understanding of One Health, and their willingness to follow government policies to prevent and control pandemics. Using numerically scaled surveys, we analyzed the relationships between these variables. We recruited 224 participants from 19 provinces in Indonesia. Our results show a strong link between trust built through experience and understanding of One Health, and people’s compliance with government policies. This study emphasizes the importance of educating the public about One Health and building trust to improve adherence to future pandemic prevention measures.